REPRESENTATION OF TERROR IN THE FILM 13 BOMBINGS IN JAKARTA - Agi Gimnastiar,; Anisti,; Tuty Mutiah, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to analyze the representation of mass media in disseminating information about terrorism as portrayed in the film 13 Bombs in Jakarta. The film illustrates how terrorist groups utilize media to spread fear through televised and digital threat broadcasts, while the government uses the same medium to deliver public appeals and foster social solidarity. This research employs a descriptive qualitative approach using Charles Sanders Peirce’s semiotic analysis, which includes three key elements: icon, index, and symbol. Data were collected through direct observation of film scenes that depict the role of media within the narrative. The findings reveal that mass media in the film serve a dual function: as an instrument of terror dissemination and as a tool of information control by the state. This representation reflects a social reality in which media not only deliver information but also construct narratives, shape public opinion, and influence societal perceptions of terrorism